Pengujian Software Aplikasi Perawatan Barang Milik Negara Menggunakan Metode Black Box Testing Equivalence Partitions - Nur Wahyu Rahadi; Cahya Vikasari (P3M Politeknik Negeri Cilacap, 2020)
The quality of software can be measured. One of them is by its functionality, whether it is suited to user requirements or not. To maintain the quality of the software, testing needs to be conducted during the development stage to ensure that there are no errors or bugs. Tests carried out on the state property maintenance software are focused on the functional module of item replacement by using the black box testing equivalence partitions method. The final result of this test is to know the effectiveness level of the equivalence partitioning method by determining the application test case, initializing the standard input and output partition grade and testing dataset. The final result of the application test shows that the level of effectiveness of the functional goods replacement module is 93.2%